2016
DOI: 10.1002/2016je005150
|View full text |Cite
|
Sign up to set email alerts
|

A whole new Mercury: MESSENGER reveals a dynamic planet at the last frontier of the inner solar system

Abstract: The MErcury Surface, Space ENvironment, GEochemistry, and Ranging (MESSENGER) mission yielded a wealth of information about the innermost planet. For the first time, visible images of the entire planet, absolute altimetry measurements and a global gravity field, measurements of Mercury's surface composition, magnetic field, exosphere, and magnetosphere taken over more than four Earth years are available. From these data, two overarching themes emerge. First, multiple data sets and modeling efforts point toward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 95 publications
(153 reference statements)
0
13
0
Order By: Relevance
“…In fact, Raines et al, 2015 found that the concurring contribution of the SW high dynamic pressure and the weak planetary magnetic field moves the dayside magnetospheric boundaries (viz., the bow-shock and magnetopause) approximately 8 times closer to Mercury's surface with respect to the Earth's case. So, to better understand the dynamics of the Hermean magnetosphere in response to SW plasma and IMF variations, a characterization of the solar inputs is needed (e.g., James et al, 2017;Johnson & Hauck, 2016). For this reason, studies aiming to the evaluation of changes in the shape and in the dynamics of the Hermean magnetosphere should take in proper account that SW variations are not random but depend on the occurrence of specific structures traveling in space.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, Raines et al, 2015 found that the concurring contribution of the SW high dynamic pressure and the weak planetary magnetic field moves the dayside magnetospheric boundaries (viz., the bow-shock and magnetopause) approximately 8 times closer to Mercury's surface with respect to the Earth's case. So, to better understand the dynamics of the Hermean magnetosphere in response to SW plasma and IMF variations, a characterization of the solar inputs is needed (e.g., James et al, 2017;Johnson & Hauck, 2016). For this reason, studies aiming to the evaluation of changes in the shape and in the dynamics of the Hermean magnetosphere should take in proper account that SW variations are not random but depend on the occurrence of specific structures traveling in space.…”
Section: Introductionmentioning
confidence: 99%
“…Mercury's close proximity to the Sun exposes it to the extreme solar wind conditions present at an orbital distance of 0.31–0.47 AU, including an interplanetary magnetic field (IMF) strength of 20–40 nT (Blomberg et al, ), ∼5 times that measured at Earth, and solar wind number density of 30–70 cm −3 (Blomberg et al, ), an order of magnitude greater at Mercury (Baumjohann et al, ). Furthermore, the planetary dipole moment at Mercury is about 3 orders of magnitude lower than that at Earth (Johnson et al, ; Johnson & Hauck, ), with a value of 195 nT RM3 (Anderson et al, ) (where R M =2440 km is the radius of Mercury). The combination of this weak planetary field and the solar wind conditions means the Hermean magnetosphere is extremely small and strongly driven by variable conditions in the solar wind (Slavin et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Smith et al 2012;Hiremath 2012;Hauck et al 2013;Johnson & Hauck 2016). In our simulations we assume that Mercury has a uniform resistive interior with resistivity η = 10 7 Ω × m. Since the solar wind plasma and IMF orientation and strength remain constant at the inflow boundary of the simulations presented here, and since Mercury's mantle has very low conductivity, no electromagnetic induction is generated by the interior of Mercury over a constant solar wind and IMF.…”
Section: Simulation Parameters and Assumptionsmentioning
confidence: 99%
“…Therefore, to understand the structure of Mercury's magnetosphere and its response to the solar wind plasma and IMF variations, we need to understand the interaction between the solar wind and Mercury's magnetosphere and distinguish between the contributions from external and internal magnetic sources (e.g. Raines et al 2015;Johnson & Hauck 2016;James et al 2017).…”
Section: <3mentioning
confidence: 99%
See 1 more Smart Citation